Exploratory factor analysis of the reintegration to normal living index in a stroke population. Issue 2 (17th February 2017) - Merz, Zachary C.; Van Patten, Ryan; Mulhauser, Kyler; Fucetola, Robert
Abstract : Background: The reintegration to normal living index (RNLI) is a global assessment of patient quality of life often utilized in stroke populations. Previous studies in various general disability samples have consistently reported a two-factor solution for the RNLI. Despite its common use with stroke patients, the RNLI has not been psychometrically evaluated in an exclusively stroke sample. This study is believed to represent the first factor analysis of the RNLI using a sample comprised exclusively of individuals who have survived cerebral infarct. Objective: The aim of this study is to evaluate the psychometric properties of the RNLI in assessing quality of life of stroke survivors. Methods: We retrospectively examined RNLI scores of 928 adults with strokes of varying severities as part of a multidisciplinary, interinstitutional collaboration across an academic medical center, acute care hospital, and rehabilitation center. We utilized a principal component factor analysis to evaluate the factor structure of the RNLI. Results: Mean RNLI scores ±SD for the sample were 75.26 ± 19.85, ranging between 20 and 100. The Cronbach α was .94. A scree test for factor retention strongly suggested a single factor solution, explaining 64.50% of the total variance. Conclusions: Previous factor analyses on the RNLI utilizing general disability samples commonly report a two-factor solution. Our data support the presence of a single factor solution across the RNLI within a large sample comprised exclusively of stroke survivors. This suggests that the RNLI acts as more of a unitary measure of quality of life within a stroke sample relative to other disabled samples.